ANALISIS KELAYAKAN LINGKUNGAN DALAM PEMBANGUNAN KAWASAN WATERFRONT CITY DI KOTA PEKANBARU - Adiana Sulistianto; Yusni Ikhwan Siregar; Jimmy Copriady (Jurnal Ilmu Lingkungan, 2016)
analysis environment suitability of to Develop as Waterfront City Area of Pekanbaru City. Supervised by Prof. Dr. Ir. Yusni Ikhwan, M.Sc. and Dr. Jimmy Copriady, M.Si. The research of waterfront city area was conducted in February 2014 in Pekanbaru City as stream Siak Rivers of specially among a bridge Leton 1 for until Bridge Siak III in located at sub-district office Senapelan and sub-district Rumbai Pesisir. Developing model to environment dome to be based on ecologi aspect, social culture aspect, economy aspect and organizations aspect by SWOT analysis. taking over Technique of to research etc done with purposive sampling. The research result waterfront city area in Pekanbaru City have strength of to cover weakness to become waterfront city. Developing model waterfront city for the perceived environment fisic, biology, chemistry as well as environment social culture, economy, and organizations aspect. to be based on valuing strength able to maximized for to decrease weakness, developing as condition to have an opportunity well become to waterfront city area. The alternative strategy on developing waterfront city area pekanbaru city to be empowering the public, developing of area, revalitation of river, more than lead of stakeholders coordination, maintenance of judgment as well as socialization policy. Waterfront city area to own strength etc an opportunity of to developing as suitable area of organize.